2015
DOI: 10.1016/j.jmbbm.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Microscale consolidation analysis of relaxation behavior of single living chondrocytes subjected to varying strain-rates

Abstract: AFM Strain-rate dependent response a b s t r a c t Besides the elastic stiffness, the relaxation behavior of single living cells is also of interest of various researchers when studying cell mechanics. It is hypothesized that the relaxation response of the cells is governed by both intrinsic viscoelasticity of the solid phase and fluid-solid interactions mechanisms. There are a number of mechanical models have been developed to investigate the relaxation behavior of single cells. However, there is lack of mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
(70 reference statements)
4
15
0
Order By: Relevance
“…In our previous studies21303133, it has been revealed that PHE model is a powerful and potential model to simulate single cell mechanical behavior since it can account for cellular solid-fluid interaction. Therefore, this model will be used in this study to simulate time-dependent adhesion behavior of single chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous studies21303133, it has been revealed that PHE model is a powerful and potential model to simulate single cell mechanical behavior since it can account for cellular solid-fluid interaction. Therefore, this model will be used in this study to simulate time-dependent adhesion behavior of single chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this model will be used in this study to simulate time-dependent adhesion behavior of single chondrocytes. AFM biomechanical testing with different strain-rates will be conducted since this is an effective technique to identify all the material constants for PHE model213031. In this study, the mechanical responses of chondrocytes subjected to three different strain-rates (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations